2018
DOI: 10.3390/ijms19082196
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Mutation Spectrum in ABCA4: Sixty Novel Disease Causing Variants and Their Associated Phenotype in a Large French Stargardt Cohort

Abstract: Here we report novel mutations in ABCA4 with the underlying phenotype in a large French cohort with autosomal recessive Stargardt disease. The DNA samples of 397 index subjects were analyzed in exons and flanking intronic regions of ABCA4 (NM_000350.2) by microarray analysis and direct Sanger sequencing. At the end of the screening, at least two likely pathogenic mutations were found in 302 patients (76.1%) while 95 remained unsolved: 40 (10.1%) with no variants identified, 52 (13.1%) with one heterozygous mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 74 publications
(111 reference statements)
3
17
1
Order By: Relevance
“…5 In our previous work we demonstrated that among patients carrying at least one null mutation, there is a higher prevalence of peripapillary involvement and photoreceptor impairment (ERG groups II and III). 11 In the present study the genotype-phenotype correlation did not reveal any significant association between the presence of a complex allele or of a nonsense or frameshift mutation with the quantification of the peripapillary sparing. These findings might not be surprising considering the variable effect of compound heterozygosity, splicing mutations, or hypomorphic alleles on the function of the ABCA4 protein.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…5 In our previous work we demonstrated that among patients carrying at least one null mutation, there is a higher prevalence of peripapillary involvement and photoreceptor impairment (ERG groups II and III). 11 In the present study the genotype-phenotype correlation did not reveal any significant association between the presence of a complex allele or of a nonsense or frameshift mutation with the quantification of the peripapillary sparing. These findings might not be surprising considering the variable effect of compound heterozygosity, splicing mutations, or hypomorphic alleles on the function of the ABCA4 protein.…”
Section: Discussioncontrasting
confidence: 62%
“…Most of the molecular analyses were performed at the Institut de la Vision, Sorbonne Université, Institut National de la Santé et de la Recherche Médicale (INSERM), with a combination of microarray analysis and Sanger sequencing of ABCA4 as previously reported. 11 Evidence of any other pathology involving the macula and/or the optic nerve was an exclusion criterion in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Both the mutational analysis and the assessment of the healthy retina perfusion status might have pivotal importance in selecting the potential candidates for gene therapy in future trials. 5 Nassisi et al 17 compared the clinical characteristics (namely the BCVA, the central retinal thickness, and the macular volume on OCT) between patients with null and missense mutations, and found no relevant differences. On the contrary, Fujinami and associates 2 suggested a potential association between nonsense genetic variants and more progressive FAF patterns; more recently, a significant association between more severe genotype categories and faster progression of disease on OCT has been described.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were divided in two genotype groups: (1) patients with at least one null mutation (NM), comprising frame-shift or nonsense mutations or all genetic variants affecting splicing producing a premature stop of the wild-type protein; (2) patients with two or more missense mutations (MM). 17…”
Section: Genetic Testingmentioning
confidence: 99%
“…For example, Stargardt disease is a macular dystrophy with a prevalence of ~1:8000–10,000 predominantly caused by biallelic variants in ABCA4 , which determine the onset and severity of the phenotype. 18 , 19 Some disease-causing variants in the same gene can be associated with syndromic or nonsyndromic disorders, for example, USH2A biallelic variants can be associated with type II Usher syndrome in 85% of cases, characterised by vision and hearing loss, or nonsyndromic RP in 20% of RP cases. 20 22 Although the majority of bilateral microphthalmia/anophthalmia cases are due to dominant monoallelic mutations, homozygous and compound heterozygous loss-of-function variants are found in STRA6 and RAX .…”
Section: How To Identify Patients Who May Benefit From Genetic Screenmentioning
confidence: 99%